2010
DOI: 10.1002/cbf.1680
|View full text |Cite
|
Sign up to set email alerts
|

SR‐BI, CD36, and caveolin‐1 contribute positively to cholesterol efflux in hepatic cells

Abstract: In non-hepatic cells, scavenger receptor class B type I (SR-BI), cluster of differentiation 36 (CD36), and caveolin-1 were described as mediators of cholesterol efflux, the first step of reverse cholesterol transport (RCT). Stable transformants of HepG2 cells overexpressing SR-BI, CD36, or caveolin-1 were generated, as well as cells overexpressing both caveolin-1 and SR-BI or caveolin-1 and CD36 in order to address the effect of caveolin-1 on both receptor activities. These cells were analyzed for their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
2
16
1
Order By: Relevance
“…This is in line with the well-known function of SR-BI in mediating selective lipid uptake from HDL particles. In contrast to our fi nding that SR-BI decreases cholesterol effl ux to apoA-I, a recent study demonstrated that SR-BI in hepatocytes can promote cholesterol effl ux to human HDL 3 ( 49 ). The different effects of SR-BI on cholesterol effl ux in the two studies are likely due to differences in the abilities of lipid-poor apoA-I and HDL 3 in promoting cholesterol effl ux.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in line with the well-known function of SR-BI in mediating selective lipid uptake from HDL particles. In contrast to our fi nding that SR-BI decreases cholesterol effl ux to apoA-I, a recent study demonstrated that SR-BI in hepatocytes can promote cholesterol effl ux to human HDL 3 ( 49 ). The different effects of SR-BI on cholesterol effl ux in the two studies are likely due to differences in the abilities of lipid-poor apoA-I and HDL 3 in promoting cholesterol effl ux.…”
Section: Discussioncontrasting
confidence: 99%
“…However, recent work has demonstrated that (neonatal) ventricular myocytes control cholesterol predominantly through cholesterol efflux rather than internalisation of native or acetylated LDL [11]. These authors focused on the ABC transporters as cholesterol efflux pathways, however caveolin has also been linked with cholesterol efflux to HDL [36], [37]. Here we show further evidence for a cholesterol-dependent control of efflux pathways.…”
Section: Discussionsupporting
confidence: 59%
“…Other proteins have been described to contribute to cellular cholesterol efflux in different cell types, including the scavenger receptor B1 (SR-BI), CD36 and Caveolin-1 (Cav-1) [51]. However, their contribution to macrophage RCT in vivo is not clear and remains uncertain [52].…”
Section: Cholesterol Homeostasis Cholesterol Efflux and Reverse Cmentioning
confidence: 99%
“…As lipid droplet cholesteryl ester hydrolysis is being recognized as an important step in cholesterol efflux [56], miRNAs that target key pathways in lipid-loaded macrophage autophagy and/or cholesterol ester hydrolases might be interesting targets to promote cholesterol efflux. Caveolin has been proposed to contribute to cellular cholesterol efflux [51,160]. Several miRNAs including, miR-103, miR-107, miR-133a, miR-802 and others were validated to target Cav-1 [161,162].…”
Section: Mirna Targets In Cholesterol Efflux Reverse Cholesterol mentioning
confidence: 99%